Peran Kebijakan Investasi dalam Strategi Peningkatan Pendapatan Asli Daerah (PAD) di Kabupaten Sigi - Handayani, Fany Arista; Burhanuddin, Burhanuddin; Mande, Henni; Said, Rosnani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2025)
Regional Original Revenue (Pendapatan Asli Daerah, PAD) is a key indicator of fiscal independence and a measure of local government capacity to finance development and public services. Sigi Regency possesses significant economic potential, particularly in the agricultural, tourism, and natural resource-based industrial sectors, yet its PAD contribution remains relatively low compared to transfers from the central government. This study aims to analyze the role of investment policies of the Sigi Regency Government in supporting PAD enhancement and to formulate sustainable investment policy strategies.The study employs a qualitative approach with a descriptive design, utilizing secondary data from legal documents, academic literature, and official government publications. Analysis is conducted descriptively using the SOAR (Strengths, Opportunities, Aspirations, Results) framework to develop PAD improvement strategies based on internal potential and external opportunities.The results indicate that investment policies in Sigi Regency play a strategic role in strengthening regional fiscal capacity through the management of agriculture, mining, and tourism sectors. However, limited regulatory coverage, lack of technical guidelines, and suboptimal sectoral diversification remain major challenges. The proposed investment policy strategies emphasize the utilization of natural resource potential and social capital, development of community-based leading sectors, digitalization of fiscal and licensing services, and strengthening investment infrastructure and governance.